Cena milosci Ojczyzny - Popieluszko, Jerzy, 1947-1984. ([Rome : s.n., 1984)
Sermons and homilies of Fr. Popieluszko, as well as a brief biography of the priestwho was murdered by the communist segment of the Polish government in 1984.
"Ten zbior jego homilii skladaja w holdzie rzymscy przyjaciele"--P. opposite t.p.
Cover portrait.
Keywords: Catholic Church -- Sermons; Sermons, Polish; Poland -- Social conditions -- 1980-; Poland -- Politics and government -- 1980-1989.